An innovative approach for identification of pivotal node in terrorist network using promethee method (an anti-terrorism approach) - Singh, Saurabh; Verma, Shashikant; Tiwari, Akhilesh (International Journal of Engineering and Technology, 2018)
Terrorist network analysis is vital for intelligence analysis and for deriving useful information from available raw data. Computer Science and Graph Theory provide instructive tools for the study and graphical interpretation of these networks. In this paper, we examine the 26/11 Mumbai attack terrorist network dataset and employ the Preference Ranking Organization Method for Enrichment of Evaluation (PROMETHEE) for identification of key node on the terrorist network. PROMETHEE is an effective multi-criteria decision-making model. It provides a framework to find the most suitable alternative by integrating the quantitative and qualitative factors to the decision problem and facilitates easy computation. From the 26/11 Mumbai attacks data set of terrorist network. It is found that out of several terrorists in the network â€œWassiâ€ was the focal actor. Based on the PROMETHEE framework, it is resolved that the obtained terrorist nodes can be instrumental for the intelligence and law enforcement agencies to confine their focus on important members of the terrorist network which can deter the functioning of these networks.